INTEGRATED COMMUNICATION: MARKETING COMMUNICATION IN THE INTERACTIVE AGE - Andre Hardjana (Atma Jaya Indonesia Catholic University, Jakarta, 2012)
Globalization has affected on how we communicate and what media to use in communicating. To be able to manage organizational results, many realize that individual communication held by different units did not make the organization effective nor efficient. Communication needed to be realigned and integrated to a centralized corporate communication network. In addition, with pressure from the growth of communication technology, businesses must also face the complexity and intricacy of business competitiveness and positioning to be in the minds of consumers. Hence, the development of integrated marketing communication (IMC) provided another stage of development in the communication industry.Globalization has affected on how we communicate and what media to use in communicating. To be able to manage organizational results, many realize that individual communication held by different units did not make the organization effective nor efficient. Communication needed to be realigned and integrated to a centralized corporate communication network. In addition, with pressure from the growth of communication technology, businesses must also face the complexity and intricacity of business competitiveness and positioning to be in the minds of consumers. Hence, the development of integrated marketing communication (IMC) provided another stage of development in the communication industry.